ISLAM MEMANDANG HAK ASASI PENDIDIKAN - Imam Machali (Jurnal Pendidikan Islam, 2012)
Fulfilling the education right in Indonesia as stated in the constitution faces a lot of problems. The problems include lagislation and policy, budgeting of education , fair distribution and easy access to education covering gender equality in getting and accessing education in area of conflict, boundaries, and remoted area. Problem of legislation related to law and national education policy and noble ideal of independence and the Constitution 1945, Instrument and National and International Standard of Human Right which are not in line yet, results in the condition that the education development is not based on the human right. The education budgeting relates to government commitment to allocate the amount based on the law, fair distribution and wide access to education covering the unit capacity and providing equal opportunities to all learners from different social, economic background, place of living, intelectual capacity, physical condition and gender. Those problems lead to unfulfilled education right as stated independece goals.